Collegial Support from a Maori Perspective: A Model for Counsellor Kinship - lep, Bill Anderson; Kottler, Jeffrey A.; Montgomery, Marilyn J. (Canadian Journal of Counselling and Psychotherapy, 2007)
Counsellors sometimes strugge with personal or professional challenges, stresses, and strains, a situation that can be made more difficult by a lack of support among colleagues. Finding an alternative community of support can make a crucial difference for a counsellor's well being. As a model for such a community, we look to the Maoris of New Zealand, whose kinship networks include collegial relationships within extended families of affiliation. Recommendations are drawn from this model for expanding counsellors' support systems.